Analysis of spatiotemporal variations and effects of regional functions in rural China. (25th March 2022) - Wen, Qi; Shen, Caiting; Xia, Siyou; Wang, Yongsheng
Abstract: This study analyzes the spatiotemporal evolution and effects of regional functions in rural China and summarizes the spatiotemporal characteristics of rural Chinese regional functions from 2005 to 2015. The results of this study are as follows. (a) The values of the regional functions of rural China generally exhibit a "V‐shaped" distribution such that these values are high in eastern and western China and low in central China, and are high in northern China and low in southern China. (b) The overall functions of rural Chinese regions vary distinctly by region across northeastern China, eastern China, central China, and western China. (c) The spatial variation of regional production function values in rural China also exhibits a gradually declining trend, with the highest values in eastern China, followed by northeastern, central, and western China. This pattern exhibits a relatively strong coupling relationship with the spatial variation principles governing China's natural environment, resource carrying capacity, and economic development level. Overall, regional ecological function values do not exhibit any significant variation, but they do exhibit a gradually declining trend, starting from western and northern China and moving to eastern and southern China. (d) The degree of spatial spillover received by a given region from a neighboring region's production, living, or ecological function is stronger than the effect of the error shock from the corresponding function of the neighboring region. The effects of influencing factors on different regions exhibit significant variation.